The influence of janji jiwa coffee’s brand image on consumer purchase decisions: A consumer psychology approach in Pekanbaru - Arfah, Lita (Trigin Publisher, 2025)
The brand image significantly impacts customer purchasing decisions, especially within the competitive specialty coffee sector. Janji Jiwa Coffee has cultivated a robust market presence; nevertheless, few research have investigated the influence of its brand image on consumer behavior from a psychological standpoint. Comprehending these psychological variables might assist organizations in optimizing their branding strategy and augmenting client loyalty. This study examines the influence of Janji Jiwa Coffee’s brand image on customer purchasing decisions in Pekanbaru, focusing on the roles of brand perception, brand trust, and emotional attachment in determining consumer preferences. Data were acquired from Janji Jiwa Coffee users using a quantitative technique via structured surveys. Statistical research was utilized to investigate the correlations between essential branding elements and purchasing decisions. The findings indicate that brand perception is the predominant influence, underscoring the significance of brand reputation and consistency. Brand trust profoundly affects purchasing intentions, underscoring the importance of ethical standards and product excellence in fostering loyalty. Furthermore, emotional attachment amplifies consumer involvement and fosters repeat purchases. The results underscore the necessity for strategic branding, trust-enhancing measures, and experiential marketing to bolster brand loyalty and influence customer choices.